The impact of work environment and motivation on teachers’s discipline level - Setyani Setyani (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The study aims to determine the impact of work environment and motivation on  teachers’s discipline level at SMAN 1 Abab. This study uses a quantitative study technique, that involves 56 teachers at SMAN 1 Abab. Data collection techniques used questionnaire that filled out by teachers. Studies have shown that work environment and motivations affect teacher discipline levels.